2011
DOI: 10.1128/mcb.05182-11
|View full text |Cite
|
Sign up to set email alerts
|

Key Functional Regions in the Histone Variant H2A.Z C-Terminal Docking Domain

Abstract: The incorporation of histone variants into nucleosomes represents one way of altering the chromatin structure to accommodate diverse functions. Histone variant H2A.Z has specific roles in gene regulation, heterochromatin boundary formation, and genomic integrity. The precise features required for H2A.Z to function and specify an identity different from canonical H2A remain to be fully explored. Analysis of the C-terminal docking domain of H2A.Z in Saccharomyces cerevisiae using epistatic miniarray profile (E-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 54 publications
10
45
1
Order By: Relevance
“…In the past 2 years, the importance of the H2A.Z C-terminus for nucleosome stability and chromatin association has been explored in S. cerevisiae and humans (20,21,178). Two studies in S. cerevisiae revealed that C-terminal deletions, depending on the extent of truncation, decrease or completely abolish chromatin association (23,178).…”
Section: The Influence Of H2a Variants On Nucleosome Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 2 years, the importance of the H2A.Z C-terminus for nucleosome stability and chromatin association has been explored in S. cerevisiae and humans (20,21,178). Two studies in S. cerevisiae revealed that C-terminal deletions, depending on the extent of truncation, decrease or completely abolish chromatin association (23,178).…”
Section: The Influence Of H2a Variants On Nucleosome Stabilitymentioning
confidence: 99%
“…Two studies in S. cerevisiae revealed that C-terminal deletions, depending on the extent of truncation, decrease or completely abolish chromatin association (23,178). As expected, loss of chromatin association leads to phenotypes similar to the complete knock-out of the H2A.Z gene in S. cerevisiae , such as reduced resistance to genotoxic stress and spreading of heterochromatin into euchromatic regions, indicating that chromatin association is essential for H2A.Z function.…”
Section: The Influence Of H2a Variants On Nucleosome Stabilitymentioning
confidence: 99%
“…Although such approaches are valuable for exploring the functionality of essential genes, they usually address the problem at the whole-protein level and do not identify the parts of proteins that are responsible for specific interactions or functions. However, a few studies have shown that genetic and chemogenetic interaction profiling can be extremely useful in this context 98100 , particularly for investigating the functional consequences of PTMs 98102 that may not be detectable in the protein–protein interaction network. This can be achieved by mutating the specific residues that are subject to PTM, such that they mimic either their modified or unmodified state.…”
Section: High-resolution (Chemo)genetic Interactionsmentioning
confidence: 99%
“…These results indicate that genetic interaction screening can be used not only to identify the consequences of mutating specific residues but also to identify how combinatorial perturbations of the same gene can result in unique outcomes. Genetic interaction screening has also been used to study H2A.Z using truncations of varying lengths in S. cerevisiae 102 or using targeted mutation in Schizosaccharomyces pombe 103 .…”
Section: High-resolution (Chemo)genetic Interactionsmentioning
confidence: 99%
“…Each of the histones has an N-terminal tail with a specific sequence of amino acids, but the H2A also has a C-terminal tail 12. The C-terminus forms a globular docking domain that is packaged into the core 13. Several studies have demonstrated the importance of the histone tails for nucleosome remodeling by ATP-dependent chromatin remodeling factors 14,15…”
Section: Epigenetic Regulation Of the Genomementioning
confidence: 99%